Anilide activation of adjacent C-H bonds in the palladium-catalysed Fujiwara-Moritani reaction. - Rauf, W; Thompson, A; Brown, J (2010)
The Pd(II)-catalysed oxidative counterpart of the Heck reaction, originally described by Fujiwara and Moritani, has been studied in detail by a combination of NMR, single-crystal X-ray diffraction and substrate variation. The process involves a palladacycle that is a true intermediate in catalysis. Pd(OAc)(2) is first converted into a more electrophilic palladium species for effective catalysis, defining the main role of added acid. In the course of these studies, three palladacyclic intermediates have been characterised by X-ray diffraction, firstly the directly produced acetate complex 1, the camphorsulfonate complex 2, and additionally tosylate 3, isolated from a reacting system, demonstrating the accessibility of a cationic or comparably electrophilic palladium entity under turnover conditions. The isolated palladacycle 3 is also an effective catalyst. The reaction rate shows a first-order dependency on [anilide] and [Pd], but not on benzoquinone, alkene or p-TsOH. Acid, in the form of p-TsOH, is an essential component, whereas acetate is dispensable. A crossover experiment involving distinct substitution in reactant and palladacycle demonstrates that the palladacycle is directly involved in the catalysis.